ANALYSIS OF THE APPLICATION OF FINGERPRINT ATTENDANCE (FINGERSPOT) AND SERVICE CHARGE ON EMPLOYEE WORK DISCIPLINE AT LE GRANDE BALI ULUWATU HOTEL - Geraldine, Putu Prita Pramesti; Sanjaya, Ida Bagus; Saputra, Upayana Wiguna Eka (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study was conducted to examine the impact of implementing an attendance system based on fingerprint technology (Fingerspot) and the provision of service charges on the level of discipline among workers at Le Grande Bali Uluwatu Hotel. The study's object includes the entire workforce of Le Grande Bali Uluwatu Hotel, comprising 183 employees. Methods: The data collection process employed a cross-sectional design, with questionnaires distributed online through the Google Forms platform. The sampling method employed the Proportionate Stratified Random Sampling technique, resulting in a sample of 65 respondents. The characteristics of this research are classified as explanatory research using a quantitative approach. Research data processing utilizes the SPSS application to analyze the correlation between research variables. Results: The data collection strategy employed includes distributing questionnaires, reviewing the literature, and conducting direct observations. The information collected will be analyzed in a quantitative, numerical format. The analysis method used consists of Instrument Validity and Reliability Tests, Descriptive Statistical Analysis, classical assumption testing, and Hypothesis Testing. The outcome of this research is expected to provide a comprehensive picture of the correlation between the application of the fingerprint attendance system and the allocation of service charges based on the level of employee discipline. This research concludes that the application of Fingerprint Attendance (Fingerspot) and Service Charge makes a positive and significant contribution in optimizing performance and providing positive evaluations and feedback to the Human Resources Department regarding the work discipline of employees at Le Grande Bali Uluwatu Hotel. Keywords: Employee Work Discipline Fingerprint Absence, Human Resources, Service Charge